2020
DOI: 10.1177/0018578720906613
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tranexamic Acid in the Management of an Acutely Hemorrhaging Patient

Abstract: Background: Acute hemorrhage, both traumatic and nontraumatic, leads to significant morbidity and mortality, both in the United States and globally. Traditional treatment of acute hemorrhage is focused on hemostasis and blood product replacement. Tranexamic acid is an antifibrinolytic agent that may reduce acute hemorrhage through inhibition of plasminogen. Newer research suggests that coagulopathy, specifically fibrinolysis, may contribute significantly to the pathology of acute hemorrhage. Methods: We search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…In addition, smoke blocks the surgical field of view and prolongs the operative time (Gioutsos et al, 2022). Antifibrinolytic drugs, such as tranexamic acid, can also be used for local hemostasis (Davis et al, 2021). However, the dosage of tranexamic acid, mode of administration, and dosing interval affect the hemostatic effect, and high doses of tranexamic acid can cause seizures in patients (Colomina et al, 2021).…”
Section: Results Referencesmentioning
confidence: 99%
“…In addition, smoke blocks the surgical field of view and prolongs the operative time (Gioutsos et al, 2022). Antifibrinolytic drugs, such as tranexamic acid, can also be used for local hemostasis (Davis et al, 2021). However, the dosage of tranexamic acid, mode of administration, and dosing interval affect the hemostatic effect, and high doses of tranexamic acid can cause seizures in patients (Colomina et al, 2021).…”
Section: Results Referencesmentioning
confidence: 99%
“…At present, there are no guidelines that provide clear recommendations on the use of TXA for the treatment of GI bleeding [23]. However, another study suggested that TXA was not recommended for patients with acute GI bleeding until further strong evidence emerges [24]. hospital-based single-center study.…”
Section: Discussionmentioning
confidence: 99%
“…Given that this was a retrospective review, we could only infer correlations, not causality. Continued education and investigation regarding the use of 4F-PCC is necessary to maximize its clinical applications and effectiveness while maintaining patient safety, similar to the case with other agents for VKA reversal, such as vitamin K. 19 It is not uncommon for hemostatic medications, such as tranexamic acid 20 and activated factor VII, 21,22 to be administered in uncontrolled hemorrhage settings. Despite the known risks of these medications, which are predominately thromboembolic events, 23 they have been increasingly incorporated into daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…It is not uncommon for hemostatic medications, such as tranexamic acid 20 and activated factor VII, 21 , 22 to be administered in uncontrolled hemorrhage settings. Despite the known risks of these medications, which are predominately thromboembolic events, 23 they have been increasingly incorporated into daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%